Modified polyglycolic acid material, preparation method and application thereof, and modified polyglycolic acid particles, preparation method and application thereof

By using melt blending of specific components and impregnation of continuous fibers in polyglycolic acid composites, the problems of insufficient mechanical properties and poor impact resistance of polyglycolic acid composites are solved, and high strength and high impact resistance are achieved Modified polyglycolic acid material, suitable for a variety of manufacturing fields.

CN115322411BActive Publication Date: 2025-02-11CHINA ENERGY INVESTMENT CORP LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202110512987.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-05-11
Publication Date
2025-02-11
Estimated Expiration
2041-05-11

AI Technical Summary

Technical Problem

The mechanical properties of polyglycolic acid composites are insufficient and have poor impact resistance, making it difficult to meet the material requirements in the fields of 3D printing, downhole tool manufacturing, automobile manufacturing, etc.

Method used

By melt blending 30-90 parts by weight of polyglycolic acid, 0.1-1 parts by weight of antioxidant, and 0.3-8 parts by weight of compatible agent, an impregnation liquid is formed, and continuous impregnation of fibers is carried out in the impregnation liquid. , and then after being pressed roll, traction and air-cooled, the modified polyglycolic acid material was obtained. The specific components and treatment methods of this material reduce the difficulty of fiber impregnation, achieving regular fiber distribution and improving mechanical properties.

Benefits of technology

The high strength and high impact resistance of modified polyglycolic acid materials are achieved, with elastic modulus ≥10GPa, tensile strength ≥130MPa, and notch impact ≥40kJ/m2, which is suitable for 3D printing and manufacturing of high-demand materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003061040700000041
    Figure BDA0003061040700000041
  • Figure BDA0003061040700000091
    Figure BDA0003061040700000091
  • Figure BDA0003061040700000101
    Figure BDA0003061040700000101
Patent Text Reader

Abstract

The present invention relates to the field of polyglycolic acid modification, and discloses a modified polyglycolic acid material, a preparation method and application thereof, and a modified polyglycolic acid particle, a preparation method and application thereof. The preparation method of the modified polyglycolic acid material comprises the following steps: 1) melt-blending 30-90 parts by weight of polyglycolic acid, 0.1-1 parts by weight of an antioxidant, and 0.3-8 parts by weight of a compatibilizer to obtain an impregnation solution; (2) impregnating continuous fibers in the impregnation solution, and then sequentially passing through a pressing roller, traction, and air cooling to obtain a modified polyglycolic acid material. The modified polyglycolic acid material obtained by the present invention has excellent mechanical properties, high elastic modulus, high tensile strength, and strong notched impact performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of polyglycolic acid modification, and in particular to a modified polyglycolic acid material, a preparation method and application thereof, and a modified polyglycolic acid particle, a preparation method and application thereof. Background Art

[0002] Polyglycolic acid is a biodegradable polymer and an environmentally friendly material, which is often used to prepare composite materials. When preparing composite materials, polyglycolic acid is generally mixed with various inorganic powders (such as silica, fly ash) or short-cut fibers and then melt-extruded and granulated.

[0003] Since polyglycolic acid has poor compatibility with inorganic powder, the addition of inorganic powder has little effect on improving mechanical properties. The aspect ratio of chopped fibers is generally small, and the effect on improving mechanical strength is also limited, which is basically not beneficial to improving the impact resistance of composite materials.

[0004] The mechanical properties of polyglycolic acid composite materials are insufficient and the impact resistance is poor, which makes it difficult for polyglycolic acid composite materials to meet the material requirements in the fields of 3D printing, downhole tool manufacturing, automobile manufacturing, etc. Therefore, it is urgent to provide a high-strength, high-impact polyglycolic acid material and a preparation method thereof. Summary of the invention

[0005] The purpose of the present invention is to overcome the defect of poor mechanical properties of polyglycolic acid materials in the prior art, and to provide a modified polyglycolic acid material and a preparation method and application thereof, as well as modified polyglycolic acid particles and a preparation method and application thereof.

[0006] In order to achieve the above object, the first aspect of the present invention provides a method for preparing a modified polyglycolic acid material, the method comprising the following steps:

[0007] (1) melt-blending 30-90 parts by weight of polyglycolic acid, 0.1-1 parts by weight of an antioxidant, and 0.3-8 parts by weight of a compatibilizer to obtain an impregnation solution;

[0008] (2) immersing the continuous fiber in the impregnation liquid, and then sequentially passing through a pressing roller, pulling and air cooling to obtain a modified polyglycolic acid material;

[0009] Among them, the weight average molecular weight of the polyglycolic acid is 80,000-300,000 g / mol, and the melt index at 240°C and 2.16 kg load is 5-100 g / 10 min; the antioxidant is selected from at least one of hindered phenol antioxidants, phosphite antioxidants and thioester antioxidants; the compatibilizer is selected from at least one of epoxy compounds, maleic anhydride polymers and isocyanate compounds.

[0010] The second aspect of the present invention provides a modified polyglycolic acid material prepared by the method described in the first aspect of the present invention.

[0011] The third aspect of the present invention provides an application of the modified polyglycolic acid material described in the second aspect of the present invention in 3D printing.

[0012] The fourth aspect of the present invention provides a method for preparing modified polyglycolic acid particles, the method comprising: preparing a modified polyglycolic acid material using the method for preparing the modified polyglycolic acid material described in the first aspect of the present invention; and cutting and granulating the modified polyglycolic acid material to obtain modified polyglycolic acid particles with a length of 5-40 mm.

[0013] The fifth aspect of the present invention provides modified polyglycolic acid particles prepared by the method described in the fourth aspect of the present invention.

[0014] The sixth aspect of the present invention provides a use of the modified polyglycolic acid particles described in the fifth aspect of the present invention in the preparation of downhole tools and automobile parts.

[0015] By adopting the above technical solution, the beneficial technical effects of the present invention are as follows:

[0016] 1) The preparation method of the modified polyglycolic acid material and modified polyglycolic acid particles provided by the present invention reduces the difficulty of impregnating polyglycolic acid on continuous fibers by selecting specific polyglycolic acid, specific antioxidant and compatibilizer, and accurately controlling the content of each component, thereby obtaining a modified polyglycolic acid material and modified polyglycolic acid particles with regular fiber distribution and excellent mechanical properties, which are suitable for industrial promotion;

[0017] 2) The elastic modulus of the modified polyglycolic acid material provided by the present invention is ≥10GPa, the tensile strength is ≥130MPa, and the notched impact is ≥40kJ / m 2 , with the advantages of high strength and high impact strength, it can solve the problem of low strength or high brittleness of materials in 3D printing;

[0018] 3) The elastic modulus of the modified polyglycolic acid particles provided by the present invention is ≥8GPa, the tensile strength is ≥120MPa, and the notched impact is ≥10kJ / m 2 , and has good application prospects in the preparation of downhole tools and automotive parts. DETAILED DESCRIPTION

[0019] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0020] The first aspect of the present invention provides a method for preparing a modified polyglycolic acid material, the method comprising the following steps:

[0021] (1) melt-blending 30-90 parts by weight of polyglycolic acid, 0.1-1 parts by weight of an antioxidant, and 0.3-8 parts by weight of a compatibilizer to obtain an impregnation solution;

[0022] (2) immersing the continuous fiber in the impregnation liquid, and then sequentially passing through a pressing roller, pulling and air cooling to obtain a modified polyglycolic acid material;

[0023] Among them, the weight average molecular weight of the polyglycolic acid is 80,000-300,000 g / mol, and the melt index at 240°C and 2.16 kg load is 5-100 g / 10 min; the antioxidant is selected from at least one of hindered phenol antioxidants, phosphite antioxidants and thioester antioxidants; the compatibilizer is selected from at least one of epoxy compounds, maleic anhydride polymers and isocyanate compounds.

[0024] The inventors of the present invention have found through research that the interaction between a specific polyglycolic acid and a specific antioxidant and a compatibilizer can reduce the difficulty of impregnating the polyglycolic acid on continuous fibers, thereby obtaining a modified polyglycolic acid material with regular fiber distribution and excellent mechanical properties.

[0025] In step (1):

[0026] In a preferred embodiment, 40-70 parts by weight of polyglycolic acid, 0.2-0.5 parts by weight of antioxidant and 2-5 parts by weight of compatibilizer are melt-blended to obtain an impregnation solution.

[0027] Among them, when the contents of polyglycolic acid, antioxidant and compatibilizer are within the above preferred ranges, the comprehensive performance of the obtained modified polyglycolic acid material is optimal.

[0028] In a preferred embodiment, the weight average molecular weight of the polyglycolic acid is 150,000-300,000 g / mol, and the melt index at 240° C. and 2.16 kg load is 10-80 g / 10 min.

[0029] In a preferred embodiment, the antioxidant is a phosphite antioxidant; wherein the phosphite antioxidant is selected from antioxidant 168 and / or antioxidant 626, preferably antioxidant 168.

[0030] In a preferred embodiment, the epoxy compound is a copolymer containing a glycidyl methacrylate group, selected from at least one of styrene-acrylonitrile-glycidyl methacrylate copolymer, ethylene-methyl acrylate-glycidyl methpropionic acid copolymer, ethylene-ethyl acrylate-glycidyl methacrylate copolymer, POE elastomer-glycidyl methacrylate copolymer, and styrene-methacrylate-glycidyl methacrylate copolymer, preferably styrene-methyl methacrylate-glycidyl methacrylate.

[0031] In a preferred embodiment, the maleic anhydride grafted polymer is selected from at least one of maleic anhydride grafted polyethylene, maleic anhydride grafted POE, maleic anhydride grafted polypropylene, and maleic anhydride polyolefin copolymer; wherein the grafting rate of maleic anhydride grafted polyethylene, maleic anhydride grafted POE, and maleic anhydride grafted polypropylene is 0.2-5wt%, and the maleic anhydride polyolefin copolymer has a structure shown in Formula I:

[0032]

[0033] Wherein, R is H, C1-C6 alkyl, phenyl or C1-C6 alkoxy, and the weight average molecular weight of the maleic anhydride polyolefin copolymer is 4000-7000 g / mol.

[0034] In a preferred embodiment, the isocyanate compound is a polyisocyanate compound, selected from at least one of toluene-2,4-diisocyanate (TDI), hexamethylene diisocyanate (HDI), isophorone diisocyanate (IPDI), diphenylmethane diisocyanate (MDI), lysine diisocyanate (LDI) and polyisocyanates (PMDI) commonly used in the art, preferably diphenylmethane diisocyanate.

[0035] In a preferred embodiment, the compatibilizer is an epoxy compound, more preferably styrene-methyl methacrylate-glycidyl methacrylate.

[0036] In a preferred embodiment, the melt blending conditions include: the melt blending temperature is 220-250° C., preferably 225-235° C.; the melt blending speed is 100-400 r / min, preferably 150-300 r / min.

[0037] In a preferred embodiment, the melt flow rate of the impregnating liquid is 2-60 g / 10 min, preferably 10-40 g / 10 min, and more preferably 12-22 g / 10 min; the melt viscosity is 100-4000 Pa.s, preferably 250-3000 Pa.s, and more preferably 400-1500 Pa.s.

[0038] In step (2):

[0039] In a preferred embodiment, the continuous fiber has a diameter of 4-20 μm, preferably 5-18 μm; a tensile strength of ≥1500 MPa, preferably ≥1700 MPa; and an elastic modulus of ≥60 GPa, preferably ≥70 GPa.

[0040] The continuous fiber described in the present invention refers to a fiber filament with a length of at least 3 meters. Preferably, the continuous fiber is selected from at least one of continuous glass fiber, continuous carbon fiber, continuous boron fiber and continuous basalt fiber, preferably continuous glass fiber and / or carbon fiber, more preferably carbon fiber.

[0041] In a preferred embodiment, the impregnation conditions include: an impregnation temperature of 220-250° C., preferably 225-240° C.; and an impregnation time of 10-60 s, preferably 20-40 s.

[0042] In a preferred embodiment, the present invention does not specifically limit the operations of pressing rollers, traction, air cooling and granulation, and they can be performed according to conventional operations in the art, and the present invention will not elaborate on them herein.

[0043] The second aspect of the present invention provides a modified polyglycolic acid material prepared by the method described in the first aspect of the present invention.

[0044] In a preferred embodiment, in the modified polyglycolic acid material, the content of continuous fibers is 10-65wt%, preferably 25-60wt%.

[0045] In a preferred embodiment, the elastic modulus of the material is ≥10 GPa, preferably ≥12 GPa; the tensile strength is ≥130 MPa, preferably ≥140 MPa; the notched impact is ≥40 kJ / m 2 , preferably ≥50kJ / m 2 .

[0046] In a further preferred embodiment, the elastic modulus of the material is 10-110 GPa, preferably 15-110 GPa; the tensile strength is 130-2400 MPa, preferably 450-2300 MPa; the notched impact is 40-500 kJ / m 2, preferably 160-400 kJ / m 2 .

[0047] The third aspect of the present invention provides an application of the modified polyglycolic acid material described in the second aspect of the present invention in 3D printing.

[0048] Among them, the modified polyglycolic acid material in the present invention has the advantages of high strength and high impact strength, and can solve the problem of low material strength or high brittleness in 3D printing.

[0049] The fourth aspect of the present invention provides a method for preparing modified polyglycolic acid particles, the method comprising: preparing a modified polyglycolic acid material using the method for preparing the modified polyglycolic acid material described in the first aspect of the present invention; and cutting and granulating the modified polyglycolic acid material to obtain modified polyglycolic acid particles with a length of 5-40 mm.

[0050] Among them, compared with cutting the fibers and then putting them into the impregnation liquid for extrusion granulation, first adhering the impregnation liquid to the continuous fibers and then cutting and granulating them can make the fibers arranged regularly in the modified polyglycolic acid material, which is beneficial to improving the mechanical properties of the modified polyglycolic acid particles.

[0051] In a preferred embodiment, the present invention does not make any special provisions for cutting and granulation, and it can be carried out according to conventional operations in the art, and the present invention will not be described in detail here. Preferably, the length of the modified polyglycolic acid particles is 10-30 mm.

[0052] The fifth aspect of the present invention provides modified polyglycolic acid particles prepared by the method described in the fourth aspect of the present invention.

[0053] In a preferred embodiment, in the modified polyglycolic acid particles, the fiber content is 10-65 wt %, preferably 25-60 wt %.

[0054] In the present invention, the fiber content in the modified polyglycolic acid material particles can be measured by a high temperature calcination method, wherein the fiber content in the modified polyglycolic acid material particles is the same as the content of continuous fibers in the modified polyglycolic acid material.

[0055] In a preferred embodiment, the elastic modulus of the modified polyglycolic acid particles is ≥8 GPa, preferably ≥8.5 GPa; the tensile strength is ≥120 MPa, preferably ≥125 MPa; the notched impact is ≥10 kJ / m 2 , preferably ≥12kJ / m 2 .

[0056] In a further preferred embodiment, the modified polyglycolic acid particles have an elastic modulus of 8-50 GPa, preferably 13-48 GPa; a tensile strength of 120-500 MPa, preferably 160-430 MPa; and a notched impact of 10-80 kJ / m 2 , preferably 25-70 kJ / m 2 .

[0057] The sixth aspect of the present invention provides a use of the modified polyglycolic acid particles described in the fifth aspect of the present invention in the preparation of downhole tools and automobile parts.

[0058] The present invention will be described in detail below by way of examples. In the following examples,

[0059] Polyvinyl alcohol acid (PGA): provided by Shanghai Pujing Chemical Technology Co., Ltd., including PGA-1 (weight average molecular weight 200,000 g / mol, melt index at 240°C and 2.16 kg load is 45.0 g / 10 min); PGA-2 (weight average molecular weight 90,000 g / mol, melt index at 240°C and 2.16 kg load is 85.0 g / 10 min);

[0060] Antioxidant: Antioxidant 168 was purchased from Dongguan Guangsiyuan Polyurethane Materials Co., Ltd., and antioxidant 5057 was purchased from Panhua Chemical (Shanghai) Co., Ltd.

[0061] Compatibilizer: diphenylmethane diisocyanate (MDI) was purchased from Inokai; maleic anhydride polyolefin copolymer (R is phenyl) was purchased from Yushuo New Material Technology Co., Ltd., with a weight average molecular weight of 5500 g / mol and a brand name of SMA1000; styrene-methyl methacrylate-glyceryl methacrylate (ADR) was purchased from BASF, with a brand name of ADR-4468;

[0062] Continuous glass fiber (diameter 5-8 μm, tensile strength ≥ 1500 MPa, elastic modulus ≥ 60 GPa) and carbon fiber (diameter 5-8 μm, elastic modulus ≥ 350 GPa, tensile strength ≥ 2000 MPa) were purchased from China Jushi Co., Ltd.

[0063] In the following examples and comparative examples, the properties involved were tested by the following methods.

[0064] (1) Melt flow rate: measured using the GB / T 3682-2000 method;

[0065] (2) Melt viscosity: measured by rheological method at 240°C, strain 2%, and frequency 0.05 rad / s;

[0066] (3) Notched impact strength: for samples tested in accordance with GB / T1043-2008, at least 5 samples shall be tested and the average value shall be taken;

[0067] (4) Elastic modulus: Test according to GB9341-2008 method, test at least 5 samples and take the average value;

[0068] (5) Tensile strength: Tested according to GB / T1040.2-2006 method, at least 5 samples were tested and the average value was taken;

[0069] In the following examples and comparative examples, polyglycolic acid, antioxidants and compatibilizers were used after being dried.

[0070] Example 1

[0071] (1) adding polyglycolic acid, an antioxidant, and a compatibilizer into an extruder from a main feed port, and melt blending them at 225° C. and 200 rpm to obtain an impregnation liquid; wherein the composition and amount of the polyglycolic acid, the antioxidant, and the compatibilizer are shown in Table 1, and the performance parameters of the impregnation liquid are shown in Table 2;

[0072] (2) placing the continuous fiber into the above impregnation solution at 230° C. and immersing for 30 seconds, followed by rolling, pulling and air cooling to obtain a modified polyglycolic acid material;

[0073] (3) Part of the modified polyglycolic acid material was cut and granulated to obtain modified polyglycolic acid particles with a length of 12 mm.

[0074] The content of continuous fibers in the modified polyglycolic acid material is the same as the content of fibers in the modified polyglycolic acid particles. The content of fibers in the modified polyglycolic acid particles is measured by high temperature calcination, and the results are shown in Table 1.

[0075] Embodiment 2-8

[0076] Similar to Example 1, the difference is that the composition and amount of polyglycolic acid, antioxidant and compatibilizer in Examples 2-8, the fiber content in the obtained modified polyglycolic acid particles are shown in Table 1, and the performance parameters of the impregnation solution are shown in Table 2.

[0077] Comparative Examples 1-3

[0078] Similar to Example 1, the difference is that the composition and amount of polyglycolic acid, antioxidant and compatibilizer in Comparative Examples 1-3, the fiber content in the obtained modified polyglycolic acid particles are shown in Table 1, and the performance parameters of the impregnation solution are shown in Table 2.

[0079] Comparative Example 4

[0080] Similar to Example 4, except that the continuous glass fiber is cut into short fibers of 12 mm, polyglycolic acid, antioxidant and compatibilizer are put into a twin-screw extruder at a temperature of 235° C. and a rotation speed of 100 rpm for melt blending, and extrusion granulation is performed to obtain modified polyglycolic acid particles. The composition and amount of polyglycolic acid, antioxidant and compatibilizer, and the fiber content in the obtained modified polyglycolic acid particles are shown in Table 1.

[0081] Table 1

[0082]

[0083]

[0084] Table 2

[0085]

[0086]

[0087] Test Example 1

[0088] The modified polyglycolic acid materials and modified polyglycolic acid particles obtained in Examples 1-7 and Comparative Examples 1-4 were tested for elastic modulus, tensile strength, and notched impact immersion effect. The results are shown in Table 3:

[0089] Table 3

[0090]

[0091] It can be seen from the above results that the modified polyglycolic acid material and modified polyglycolic acid particles obtained by the coordination of the components with specific compositions and contents have excellent mechanical properties.

[0092] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A method for preparing a modified polyglycolic acid material, the method comprising the following steps: (1) melt-blending 30-90 parts by weight of polyglycolic acid, 0.1-1 parts by weight of an antioxidant, and 0.3-8 parts by weight of a compatibilizer to obtain an impregnation solution; (2) immersing the continuous fiber in the impregnation liquid, and then sequentially passing through a pressing roller, pulling and air cooling to obtain a modified polyglycolic acid material; The weight average molecular weight of the polyglycolic acid is 80,000-300,000 g / mol, and the melt index at 240°C and 2.16 kg load is 5-100 g / 10 min; the antioxidant is selected from phosphite antioxidants, and the phosphite antioxidant is selected from antioxidant 168 and / or antioxidant 626; the compatibilizer is selected from at least one of epoxy compounds, maleic anhydride polymers and isocyanate compounds; the length of the continuous fiber is at least greater than 3 meters; Wherein, in the modified polyglycolic acid material, the content of continuous fibers is 10-65wt%.

2. The preparation method according to claim 1, wherein The antioxidant is antioxidant 168.

3. The preparation method according to claim 1 or 2, wherein The epoxy compound is a copolymer containing a glycidyl methacrylate group, selected from at least one of styrene-acrylonitrile-glycidyl methacrylate copolymer, ethylene-methyl acrylate-glycidyl methpropionate copolymer, ethylene-ethyl acrylate-glycidyl methacrylate copolymer, POE elastomer-glycidyl methacrylate copolymer, and styrene-methacrylate-glycidyl methacrylate copolymer.

4. The preparation method according to claim 1, wherein The maleic anhydride polymer is selected from at least one of maleic anhydride grafted polyethylene, maleic anhydride grafted POE, maleic anhydride grafted polypropylene, and maleic anhydride polyolefin copolymer.

5. The preparation method according to claim 1, wherein the isocyanate compound is a polyisocyanate compound, selected from at least one of toluene-2,4-diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, diphenylmethane diisocyanate, lysine diisocyanate and polyisocyanate.

6. The preparation method according to claim 1, wherein The melt flow rate of the impregnation liquid is 2-60 g / 10 min, and the melt viscosity is 100-4000 Pa.s.

7. The preparation method according to claim 6, wherein: The melt flow rate of the impregnation liquid is 10-40 g / 10 min, and the melt viscosity is 250-3000 Pa.s.

8. The preparation method according to claim 1, wherein The continuous fiber has a diameter of 4-20 μm, a tensile strength of ≥1500 MPa, and an elastic modulus of ≥60 GPa.

9. The preparation method according to claim 8, wherein: The continuous fiber has a diameter of 5-18 μm, a tensile strength of ≥1700 MPa, and an elastic modulus of ≥70 GPa.

10. The preparation method according to claim 1, wherein: The continuous fiber is selected from at least one of continuous glass fiber, continuous carbon fiber, continuous boron fiber and continuous basalt fiber.

11. A modified polyglycolic acid material prepared by the preparation method according to any one of claims 1 to 10.

12. The modified polyglycolic acid material according to claim 11, wherein The modified polyglycolic acid material has an elastic modulus of ≥10 GPa, a tensile strength of ≥130 MPa, and a notched impact of ≥40 kJ / m 2 .

13. The modified polyglycolic acid material according to claim 12, wherein: The modified polyglycolic acid material has an elastic modulus of ≥12 GPa, a tensile strength of ≥140 MPa, and a notched impact of ≥50 kJ / m 2 .

14. Use of the modified polyglycolic acid material according to any one of claims 11 to 13 in 3D printing.

15. A method for preparing modified polyglycolic acid particles, comprising: Using the preparation method of the modified polyglycolic acid material according to any one of claims 1 to 10 to prepare the modified polyglycolic acid material; as well as The modified polyglycolic acid material is cut and granulated to obtain modified polyglycolic acid particles with a length of 5-40 mm.

16. Modified polyglycolic acid particles prepared by the preparation method according to claim 15.

17. The modified polyglycolic acid particles according to claim 16, wherein The modified polyglycolic acid particles have an elastic modulus of ≥8 GPa, a tensile strength of ≥120 MPa, and a notched impact of ≥10 kJ / m 2 .

18. The modified polyglycolic acid particles according to claim 17, wherein The modified polyglycolic acid particles have an elastic modulus of ≥8.5 GPa, a tensile strength of ≥125 MPa, and a notched impact of ≥12 kJ / m 2 .

19. Use of the modified polyglycolic acid particles according to any one of claims 16 to 18 in the preparation of downhole tools and automobile parts.

Citation Information

Patent Citations

  • Method and device for preparing unidirectional continuous carbon fiber reinforced thermoplastic 3D printing consumables

    CN111976141A

  • Polyglycolic acid copolymer composition and preparation thereof

    WO2020087216A1